Study of self-medication status among referring patients to Kashan pharmacies - Hadi Hayati; Bahman Khosravi; Abbas Kebriaeezadeh; Mahdi Khanizade (Tehran University of Medical Sciences, 2015)
Background: Self-medication is one of the largest social, economic and health problems in developing communities such as Iran. It is considered as an unsafe treatment behavior. This study aimed to assess self-medication status among referring patients to Kashan pharmacies. Methods: This descriptive cross-sectional study was conducted in 2012; 12 pharmacies were selected randomly from 56 pharmacies in Kashan. The data was collected through observation, interviews and semi-structured questionnaire. The data were analyzed through SPSS v.18. Results: About 26% of patients requested drug without a prescription. Of 208 persons, 143 persons (%68.8) were men, and 65 (31.3%) women; 119 (57.2%) had high school or academic education. The most requested drugs were analgesics (36.5%), antibiotics (30.8%), cold remedies (16.8%), gastrointestinal (513.5%), tranquilizers and antidepressants (11.5%). Main excuses for self-medication were having previous experience of using the drug (46.7%) and low importance of the disease (25%). Conclusion: In Iran, the rate of self-medication is very high and analgesics and antibiotics are among the most without-prescription requested drugs. Clearly, providing help to raise public awareness on the over-the-counter (OTC) drugs and prescription-only medicines' (POM) risks and side effects is needed. According to the reasons mentioned for self-medication immediate action for reducing nonprescription medicine request are essential.